A case report of giant anterior neck lipoma - Jain, Shalini; Maingi, Sahil; Sofia, Ancy S.; Rai, A. K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Lipoma is a benign mesenchymal tumor with a thirteen percent incidence in head and neck region. Posterior triangle is the most common location while anterior neck lipoma is a rare one. Giant lipomas >10 cm have been reported in different parts of the body but rarely in the anterior neck. Surgical excision remains the treatment of choice. We here report a case of giant anterior neck lipoma in a 50 year old male managed surgically.